AB0264 The perforin A91V gene and clinical features analysis in chinese SO-JIA cases with macrophage activation syndrome. (15th June 2017) - Wei, P; Zeng, H
Abstract : Objectives: Macrophage activation syndrome (MAS) is a severe, potentially fatal complication of rheumatoid disease, especially in the systemic onset juvenile idiopathic arthritis (SoJIA). we aimed to investigate the clinical characteristics of 31 SOJIA cases with MAS and the perforin A91V gene were detected in part cases Methods: gene-specific polymerase chain reaction (PCR) primers were used to analyze the perforin A91Vgene polymorphism. Results: 31 soJIA cases were associated with MAS.25 out of 31 cases (83%) had infections prior to MAS. Serum ferritin was significantly increased in 27 cases (87.10%). High concentrations of triglycerides (23cases, 74.19%) and lactic dehydrogenase (27cases, 87.10%) are observed. What is more, Creatine Kinase (CK) increased in all cases that had been checked. Well-differentiated macrophages phagocytosing hematopoietic elements were found in all cases (100%).6 cases (19.35%) merged with multiple organ dysfunctions (MODS). The perforin A91V (NCBI: SNP rs35947132) variant gene was detected in twenty cases, but no mutation was found. Corticosteroids, immunosuppressant, cell cycle inhibitors, immunoglobulin, Tumor necrosis factor (TNF) antagonist and plasmapheresis were effective. After treatment, 28cases (90.32%) children were in remission, while 3 out of 31 cases died with mortality of 9.68%. Conclusions: MAS is a life-threatening complication of systemic onset juvenile idiopathic arthritis. Most cases were preceded by infection. Unremitted fever, progressive hepatosplenomegaly, lymphadenopathy, cytopenias, elevated serum liver enzymes significantly increased serum ferritin are the main feature. Early diagnosis and treatment is the key to improve prognosis. The perforin gene mutations in our patients have not found yet. Disclosure of Interest: None declared